Respiratory chronic health conditions and racial disparities associated with e-cigarette use: a cross-sectional analysis using behavioral risk factor surveillance data - Comiford, Ashley; Pan, Steven; Chen, Sixia (Frontiers in Public Health, 2024)
BackgroundChronic Obstructive Pulmonary Disease (COPD), mainly caused by cigarette smoking, is one of the leading causes of death in the United States (US) and frequent asthma attacks are often exacerbated by cigarette use. Electronic cigarettes (e-cigarettes) are often used to quit cigarette smoking. Prevalence of COPD, asthma, cigarette use, and e-cigarette use differs between racial/ethnic groups. The overall objective was to assess the associations between e-cigarette use and COPD and asthma and how race/ethnicity and cigarette smoking modifies these associations.MethodsData were retrieved from the 2016–2018 and 2020–2021 Behavioral Risk Factor Surveillance System datasets, a national annual health survey representing the US general adult population. Frequency and weighted percentages or means and standard deviations were obtained. Rao-Scott Chi-square test, two-sample t tests, and logistic regression were used to evaluate binary associations between current e-cigarette use and lifetime diagnosis of COPD and asthma. Multivariable analyses using logistic regression were conducted to assess associations between variables. Interaction effects between e-cigarette use and race/ethnicity were assessed and stratified analyses were performed as indicated. All multivariate analyses were stratified by cigarette smoking status.ResultsPrevalence of e-cigarette use was 5.1%, COPD was 6.7%, and asthma was 9.2%. Individuals who currently smoked cigarettes among all racial/ethnic groups, excluding non-Hispanic (NH) American Indian/Alaska Native individuals, were more likely to report current asthma if using e-cigarettes compared to non-use (p < 0.05). Among individuals who never smoked, Non-Hispanic White (NHW), NH-Black and Hispanic individuals using e-cigarettes had greater odds of COPD compared to NHW, NH-Black and Hispanic individuals who did not use these products, respectively (p < 0.05). Among NHW, Hispanic, and NH-Other persons who currently used cigarettes, individuals currently using e-cigarettes had greater odds of COPD compared to NHW, Hispanic, and NH-Hispanic individuals who did not use e-cigarettes, respectively (p < 0.05). Among individuals who formerly used cigarettes, current e-cigarette use was associated with COPD and asthma. Among individuals who never used cigarettes, current e-cigarette use was associated with reporting current asthma.ConclusionThe association between e-cigarette use and COPD and asthma was dependent on smoking status and racial/ethnic groups. Further studies should be conducted to explore this association.